Association of a Modified Blumgart Anastomosis With the Incidence of Pancreatic Fistula and Operation Time After Laparoscopic Pancreatoduodenectomy: A Cohort Study - He, Yong-Gang; Yang, Xiao-Min; Peng, Xue-Hui; Li, Jing; Huang, Wen; Jian, Gui-Cang; Wu, Jing; Tang, Yi-Chen; Wang, Liang; Huang, Xiao-Bing (Frontiers in Surgery, 2022)
Background: To explore the association between the modified Blumgart anastomosis technique and operative time and surgical complications. Methods: This is a retrospective cohort study, and analyzed the data of patients who underwent laparoscopic pancreaticoduodenectomy from January 2015 to March 2021. The primary outcome is to explore the association between the modified Blumgart anastomosis technique and operative time. Results: A total of 282 patients were enrolled. There were 177 cases of pancreatic duct-to-mucosa anastomosis in the traditional surgery group, and 105 cases of the modified three-step Blumgart anastomosis in the modified group. There were no statistically significant differences in the general and intraoperative characteristics found between the two groups (P > 0.05). The surgical method was an independent predictor of operative time. Overall complications postsurgery were less common in the modified group than in the traditional group. The incidence of postoperative pancreatic fistula was higher in the traditional group than in the modified group (45 cases (25.4%) and 11 cases (10.5%), respectively). Fourteen cases (7.9%) in the traditional group and four case (3.8%) in the modified group had postoperative pancreatic fistula of grades B + C. The two groups had statistically significant differences (P < 0.05). The results of the linear regression showed that the type of surgical method was associated with operation time (95% CI: –73.074 to –23.941, β: -0.438, P < 0.001). Conclusion: The modified three-step Blumgart pancreaticojejunostomy was associated with the operation time.